2014
DOI: 10.5152/dir.2014.13501
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics of the proximal pulmonary arteries and vena cava in patients with chronic thromboembolic pulmonary hypertension: correlation between 3.0 T phase-contrast MRI and right heart catheterization

Abstract: ORIGINAL ARTICLE PURPOSEWe aimed to determine the correlation between flow characteristics of the proximal pulmonary arteries and vena cava obtained by 3.0 T phase-contrast magnetic resonance imaging (MRI) and hemodynamic characteristics by right heart catheterization in patients with chronic thromboembolic pulmonary hypertension. MATERIALS AND METHODSTwenty consecutive patients with chronic thromboembolic pulmonary hypertension and 20 sex-and age-matched healthy volunteers were included prospectively. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In addition, the hemodynamic changes in the large pulmonary arteries under PH have been extensively assessed in previous studies and are well summarized by Reiter U. et al [ 19 ]. In PAH, we observed the same findings as in the previous clinical studies [ 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 ], indicating that we reached the same level of accuracy. In a recent study by Cerne et al [ 32 ], the V mean of the main, right and left pulmonary arteries showed considerably lower values in PAH in comparison to the normal population.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the hemodynamic changes in the large pulmonary arteries under PH have been extensively assessed in previous studies and are well summarized by Reiter U. et al [ 19 ]. In PAH, we observed the same findings as in the previous clinical studies [ 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 ], indicating that we reached the same level of accuracy. In a recent study by Cerne et al [ 32 ], the V mean of the main, right and left pulmonary arteries showed considerably lower values in PAH in comparison to the normal population.…”
Section: Discussionsupporting
confidence: 88%
“…The main purpose of surgical CTEPH treatment is the restoration of lung perfusion through removal of thrombi and scars. As a consequence, we measured significantly increased PBF [ 10 ] and main pulmonary arterial blood flow velocities [ 7 , 18 , 19 ]. Central PBF and blood flow velocity ratios did not interrelate significantly.…”
Section: Discussionmentioning
confidence: 99%